Intra-abdominal fibrosis in a recent cohort of patients with neuroendocrine ('carcinoid') tumours of the small bowel. - Druce, MR; Bharwani, N; Akker, SA; Drake, WM; Rockall, A; Grossman, AB (2010)
BACKGROUND: Fibrosis is a hallmark of neuroendocrine tumours (NETs) arising in the jejunum and ileum and may manifest in the mesentery and elsewhere. It is clinically important and once-established, there are few effective therapies. AIM: To examine the frequency, radiological manifestations and clinical significance of intra-abdominal fibrosis in a patient cohort using modern cross-sectional imaging. Current prevalence is compared to historical series and correlation with cardiac fibrosis evaluated. DESIGN: Cross-sectional, retrospective survey of a cohort of patients with mid-gut NETs from a single centre. METHODS: Review of clinical features, biochemistry and imaging of patients with sporadic mid-gut NET and available imaging between 2002 and 2008. RESULTS: Thirty-one patients were included: 26 (83.9%) had liver metastases and 11 (35.4%) had small-bowel wall thickening; 17 patients (55%) had mesenteric involvement, with a mass, which contained coarse calcification in seven patients and fine calcification in a further two. There was soft-tissue stranding in 13 patients (plus in a further patient with no mass) and 'indrawing' of tissues in 11 patients. Two patients had a 'misty' mesentery and two had early retroperitoneal fibrosis. Mesenteric involvement was unrelated to gender and urinary 5HIAA excretion. CONCLUSION: Intra-abdominal fibrosis can be detected radiologically in around half of patients with mid-gut NET using contemporary cross-sectional imaging. Although not statistically significant, small-bowel obstruction was seen more frequently in the group with fibrosis. There was no relationship with cardiac fibrosis. Prospective studies are needed to evaluate predictors of fibrosis onset and clinical course and determine optimal methods of prevention and treatment.